2020
DOI: 10.1101/2020.08.25.267435
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNA promotes the formation of spatial compartments in the nucleus

Abstract: The nucleus is a highly organized arrangement of RNA, DNA, and protein molecules that are compartmentalized within three-dimensional (3D) structures involved in shared functional and regulatory processes. Although RNA has long been proposed to play a global role in organizing nuclear structure, exploring the role of RNA in shaping nuclear structure has remained a challenge because no existing methods can simultaneously measure RNA-RNA, RNA-DNA, and DNA-DNA contacts within 3D structures. To address this, we dev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 139 publications
3
64
0
Order By: Relevance
“…Further research of their interactions with MeCP2 are integral to understanding how they may relate to RTT. Of note, RNA has been shown to promote the formation of spatial compartments in the nucleus ( Quinodoz et al, 2020 ), and might assist MeCP2 in its formation of heterochromatin condensates ( Sheikh et al, 2016 ; Li et al, 2020 ).…”
Section: Subsectionsmentioning
confidence: 99%
“…Further research of their interactions with MeCP2 are integral to understanding how they may relate to RTT. Of note, RNA has been shown to promote the formation of spatial compartments in the nucleus ( Quinodoz et al, 2020 ), and might assist MeCP2 in its formation of heterochromatin condensates ( Sheikh et al, 2016 ; Li et al, 2020 ).…”
Section: Subsectionsmentioning
confidence: 99%
“…Recently, Quinodoz et al demonstrated this with a proximity-ligation independent technique (RD-SPRITE) that readily captures and characterizes RNA and DNA interactions within the context of chromatin domains 27,[81][82][83][84][85] . An intriguing finding is that noncoding RNA species (ncRNA) tend to spatially localize to their own sites of transcription, likely to modulate transcription through physical means 27 . One example of lncRNA-mediated spatial control of DNA and multi-locus gene expression regulation is the RNA-DNA interaction of Xist in X-chromosome inactivation of embryonic stem cells 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Yet others, such as the massive Mediator and Integrator complexes, span both roles [12][13][14][15][16][17][18][19][20] . Recent work in developmental and cancer biology has revealed that alterations in structural complexes can impact transcription in ways unrelated to genome integrity, causing developmental abnormalities and premalignant conditions [21][22][23][24][25][26][27][28][29][30][31] . In otherwise healthy organisms, viral transcriptional read-through can remodel the physical arrangement of surrounding DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Although 3C-based methods are widely used to probe 3D genome organization, the proximity ligation step required in 3C-derivatives may miss important interactions that do not occur close enough for molecules to proximity ligate to one another (Beagrie et al, 2017;Quinodoz et al, 2018Quinodoz et al, , 2020. Thus, nonproximity methods may enable mapping of structures beyond this limit.…”
Section: Sequencing-based Methods Uncover Multiple Lengths Scales Of mentioning
confidence: 99%
“…Specifically, SPRITE crosslinks RNA and DNA within the nucleus together, fragments it, then uses a ''split-pool tagging'' process to uniquely barcode each crosslinked fragment. This split-pool barcoding approach allows both RNA and DNA to be directly read, enabling the simultaneous identification of DNA-DNA, RNA-DNA, and RNA-RNA interactions (Quinodoz et al, 2018(Quinodoz et al, , 2020. Average 3D chromatin structures are similarly recapitulated by Hi-C, GAM, and SPRITE methods (Fiorillo et al, 2020).…”
Section: Sequencing-based Methods Uncover Multiple Lengths Scales Of mentioning
confidence: 99%